A centralidade e o centro como dinamizador dos territórios : os serviços de saúde em Paranavaí-PR - Santos, Regerson Franklin dos (2008)
This paper is an attempt for studying Geography as a whole, that is, relating theory to practice, by considering the epistemology, that is, the issues that involve the multi, pluri and inter-disciplinarity, without leaving apart the intrinsic relation between both systems, the object and the action. With such an attitude, it is possible to get to cohesive and efficient conclusions that express an existing reality; not the ideological vestiges in favor of the capital, which has turned the State into a mere spectator of political and economical issues. To reach that purpose, 'The Territory Use' was adopted as a category of fundamental analysis for the construction and reconstruction of geographical spaces that interconnect the world to the local place. Thus, that methodology will be applied to the present study, once the aim is to study the centrality of health services that turn Paranavai, a town in the state of Parana, into a significant regional center for the surrounding little towns or municipalities that are deprived from basic health structure. Therefore, cohesion, as well as ethics and critical attitudes, are factors that allow us to reflect upon the use of the territory, giving advantages to a few people, but keeping people in need aside, and consequently, forming a perverse and uneven space. Therefore, the Geographers' task is to join the geographies in order to build a truly space for solidarity